ChemInform Abstract: Selective Monoarylation of Primary Amines Using the Pd‐PEPPSI‐IPentCl Precatalyst. Issue 51 (December 2015) - Sharif, Sepideh; Rucker, Richard P.; Chandrasoma, Nalin; Mitchell, David; Rodriguez, Michael J.; Froese, Robert D. J.; Organ, Michael G.
Abstract: A broad spectrum of (het)aryl halides can be used in the title reaction.